Exploring the decision-making process of Chinese older adults transitioning to continuing care retirement communities: a qualitative study - Meina Yuan; Nan Ding; Jinping Zhao; Tao Xue; Xinyi Xu; Yuanshuo Ma; Jie Hu (BMC Geriatrics)
Abstract Background China’s rapidly aging population and the limitations of traditional home-based care have prompted many older adults and their families to consider Continuing Care Retirement Communities (CCRCs) as a comprehensive option. However, the decision-making process for this transition remains underexplored. This study aims to systematically explore how older adults navigate the decision to move to CCRCs, to guide service improvements and inform policy. Methods A qualitative research approach was employed, involving semi-structured in-depth interviews with 20 older adults residing in a large CCRC in Hebei, China. Data were analyzed using grounded theory methodology. Results The transition to CCRCs among Chinese older adults is a dynamic, four-phase process: (1) Intention Formation, driven by desires for independence, challenges of living alone, and crisis events; (2) Option Evaluation, shaped by care needs, financial considerations, and sociocultural and emotional factors; (3) Decision-Making, focused on selecting a specific CCRC; and (4) Post-Decision, reflecting on evaluation of the decision. Although CCRCs address practical needs, deficiencies remain in emotional support, social adaptation, and end-of-life care. Conclusions These findings enrich our understanding of CCRC decision-making in China by highlighting the ongoing influence of sociocultural values and personal autonomy throughout the process. Importantly, the need for personalized care persists throughout all stages, with particular emphasis on psychological support and cultural sensitivity in service delivery. Policy recommendations include improving affordability, accessibility, and community integration to better support older adults and their families. These insights contribute to service and policy innovation both in China and internationally.